Haar wavelet transformation and RC4 algorithm based Image Encryption - Elham YASIN; Rıdvan SARAÇOĞLU (International Journal of Applied Methods in Electronics and Computers, 2020)
Recently the protection and privacy of information or data have become a major concern to deal with. Developed coding for secure transmission and decrypting the image are steadily more needed for specific military, corrective, country defense, and various applications. Variance sorts of security information or data increment strategies are being created as of now, cryptographic systems are one basic path. Keep the message private by translating data or information into an alternative frame, such that the message is not perceivable. This study aims to expect the security image arrangement to be upgraded by following the Haar wavelet transformation and the RC4 encryption algorithm. For simplicity, the Image compression executed by Haar wavelet transformation to compress the image and to calculate high-speed performance. For image protection process, the RC4 encryption algorithm is applied that is also for secure image transformation.